Influence of leachates on permeability and removal rate of compacted clay - Ozcoban, M. Sukru; Erarslan, Ilkay; Tufekci, Nese (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2006)
Low permeability clay liners are used for protecting groundwater resources from leachates of solid and hazardous wastes. In this study, the effects of leachates on the permeability of compacted clay have been studied. Soil samples were obtained from the Kemerburgaz landfill on the European side of Istanbul. The soil samples have a hydraulic conductivity k of 1 x 10(-10) ms(-1), and a density of 1950 kg m(-3). In the experimental studies, physicochemical characterizations of compacted clay soil samples, the effects of the leachate on their permeability, and COD, SS, VSS, total P, Cu, Mn, and Fe in the influent and effluent have been analyzed, to determine the treatment capability of the compacted clay. The microstructure (micro-fabric) of the clay was studied by scanning electron microscopy. Its permeability to water was k = 8.62 x 10(-10) m/sec, and that to leachate k = 6.82 x 10(-10) m/sec. The treatment capabilities of the compacted clay, expressed as average removal percentage, were quite high, and 50% for COD, 55% for VSS, SS and TKN, 70% for total P and Mn, and 100% for Fe, respectively.
Keywords: permeability; compaction; compacted clay; leachate; landfill; Environmental Sciences & Ecology